1989
DOI: 10.1530/jrf.0.0870337
|View full text |Cite
|
Sign up to set email alerts
|

Properties of heparin binding to purified plasma membranes from bovine granulosa cells

Abstract: Summary. Bovine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Furthermore, since CXCL17 had no effect in membrane preparations this suggested the involvement of a site that was lost once intact cells were disrupted and pointed to the involvement of an accessory protein. Here we present several lines of evidence that this potential accessory protein contains glycosaminoglycans: 1) CXCL17 contains multiple highly conserved putative GAG binding domains and preparation of purified cell membranes certainly disrupts the native structure, function and/or potentially presence of GAGs 41 . 2) In support of this, the effect of CXCL17 was mimicked by known GAG binders, surfen and protamine sulphate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since CXCL17 had no effect in membrane preparations this suggested the involvement of a site that was lost once intact cells were disrupted and pointed to the involvement of an accessory protein. Here we present several lines of evidence that this potential accessory protein contains glycosaminoglycans: 1) CXCL17 contains multiple highly conserved putative GAG binding domains and preparation of purified cell membranes certainly disrupts the native structure, function and/or potentially presence of GAGs 41 . 2) In support of this, the effect of CXCL17 was mimicked by known GAG binders, surfen and protamine sulphate.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from smooth muscle cells and endothelial cells, heparins also bind to various other cell types, including granulosa cells, 17 epithelial cells, 18,19 and melanoma cells. 20 Although there is no reference (to the best of our knowledge) to heparin-binding receptors on fibroblast cells, the presence of specific heparin-binding sites (receptors) on fibroblast cells is nonetheless expected.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the additional interaction between heparin and phospholipid must have contributed to the intermolecular association of lipid-conjugated heparin and the interaction with the cell membrane to induce cell aggregation. It has been reported that heparin can attach to the cell membrane by interacting with membrane proteins or by directly interacting with phospholipids . The intermolecular association among lipid-conjugated heparin molecules was evident from the formation of aggregates by lipid-conjugated heparins themselves.…”
Section: Resultsmentioning
confidence: 99%